2016
DOI: 10.15273/pnsis.v48i2.6656
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of a Nova Scotia stream to enhance Atlantic salmon provides few benefits to benthic invertebrates

Abstract: Stream restoration is often undertaken with the goal of improving habitat for one focal species, most often a salmonid fish such as trout or salmon. Improvements in channel structure, especially the flushing of silt from sediments, should also benefit benthic invertebrate communities, but studies to date suggest substantial changes in benthic communities following restoration are not common. In a third-order Nova Scotia stream, we examined the effect of successful restoration to improve habitat for spawning At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Extence et al, ; Friberg, Kranvang, Svendson, & Hansen, ), partial successes ( e.g. Kail et al, ; Tetu, Mitchell, Macinnis, & Taylor, ), and failures ( e.g. examples cited by Hammond, Mant, Holloway, Elbourne, & Janes, ) is essential to inform and influence the future design and planning of river restoration projects.…”
Section: Discussionmentioning
confidence: 99%
“…Extence et al, ; Friberg, Kranvang, Svendson, & Hansen, ), partial successes ( e.g. Kail et al, ; Tetu, Mitchell, Macinnis, & Taylor, ), and failures ( e.g. examples cited by Hammond, Mant, Holloway, Elbourne, & Janes, ) is essential to inform and influence the future design and planning of river restoration projects.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of restoration efforts have been monitored poorly and the documented results have been variable. While most of the studies have found positive responses of zoobenthos communities to restoration (Albertson et al, 2011; Kil & Bae, 2012; Louhi et al, 2016; Muotka et al, 2002; Pilotto et al, 2018; Suurkuukka et al, 2014; Verdonschot et al, 2016), some have reported little or no changes in the community composition (Smith et al, 2020; Tetu et al, 2016). It is also commonly reported that zoobenthos communities are heavily obscured by river restoration procedures and show lower biomass and diversity acutely after restorations (dos Reis Oliveira et al, 2019; Louhi et al, 2011; Molina‐Moctezuma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%